Medium‐term Challenges for Jobs with Equity. Issue 1 (January 2015) - Andrianov, Vladimir; Bourmpoula, Valia; Chacaltana, Juan; Dasgupta, Sukti; Duda, Marta; Ernst, Ekkehard; Haidar, Salwa; Horne, Richard; Huynh, Phu; Jafaar, Aya; Khatiwada, Sameer; Kim, Kee Beom; et al.
Abstract : The chapter analyses factors influencing medium‐term employment growth, highlighting the importance of labour force participation, occupational changes and income inequality as key determinants. The chapter also discusses the role of manufacturing employment for overall job creation and challenges that the early decline in manufacturing employment in a series of emerging economies poses for their future economic and social development.